The Illness of Vincent van Gogh: Acute Intermittent Porphyria (Out of Print) - Wilfred Arnold (Association of American Medical Colleges, 2006)
Abstract Introduction The Illness of Vincent van Gogh interactive website offers a set of structured scientific analyses to assist the participant in arriving at a keen understanding of acute intermittent porphyria, a congenital disease diagnosed in van Gogh. Methods Unit 1 summarizes the features of the time-course of van Gogh's major medical crises. Concepts such as "organized skepticism" and "working hypothesis" are defined and developed. Prompts and questions encourage the individual participant to self-dismiss irrational options and to disregard the appeals to authority that are so popular among many psychologists and art historians. Unit 2 explains the biochemistry of heme synthesis and describes the hallmarks of acute intermittent porphyria, which is the only working hypothesis to accommodate all of van Gogh's signs and symptoms. Results This self-study exercise was taken by all (N = 255) first year students at Wayne State University School of Medicine in 2005. Their answers to the three questions on the final exam indicated assimilation of the material, and the high scores indicated achievement of objectives. Discussion These results suggest that the biography of a well-known artist can facilitate the understanding of biochemical phenomena.